2018
DOI: 10.1111/1440-1681.12955
|View full text |Cite
|
Sign up to set email alerts
|

Spermidine prevents high glucose‐induced senescence in HT‐22 cells by upregulation of CB1 receptor

Abstract: Hyperglycaemia-induced neurotoxicity involved in the pathogenesis of diabetic encephalopathy and neuronal senescence is one of the worst effects of hyperglyceamic neurotoxicity. Cannabinoid receptor type 1 (CB1) has neuroprotective function in a series of neuropathy. Spermidine (Spd) has anti-aging function in many tissues. However, the role of Spd in hyperglyceamia-induced neuronal senescence remains unexplored. Therefore, we used high glucose (HG)-treated HT-22 cell as vitro model to investigate whether Spd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…Due to their higher metabolic demands, HT22 cells require higher levels of glucose in normal growth media (25 mM glucose; Ward and Ergul, 2016). We have previously confirmed that treatment of HT22 cells with HG (150 mM) for 48 h, the cell viability was decreased to 70% compared with the control group (Zhu et al, 2018). In order to eliminate the effect of HG concentration on alteration of osmolarity, we have previously found that equal concentration of mannitol (150 mM) had no significant effect on the cell viability compared with the control group (Zhu et al, 2018).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Due to their higher metabolic demands, HT22 cells require higher levels of glucose in normal growth media (25 mM glucose; Ward and Ergul, 2016). We have previously confirmed that treatment of HT22 cells with HG (150 mM) for 48 h, the cell viability was decreased to 70% compared with the control group (Zhu et al, 2018). In order to eliminate the effect of HG concentration on alteration of osmolarity, we have previously found that equal concentration of mannitol (150 mM) had no significant effect on the cell viability compared with the control group (Zhu et al, 2018).…”
Section: Discussionsupporting
confidence: 54%
“…Accumulating evidence demonstrates that long-term hyperglycemia causes neurotoxicity (Liu et al, 2014; Bahniwal et al, 2017; Li Y. et al, 2017; Renaud et al, 2018). It is well established that neuronal senescence plays a crucial role in the neurotoxicity of hyperglycemia (Sinadinos et al, 2014; Song et al, 2016; Zhu et al, 2018). Therefore, strategies to preserve neuronal cells by increasing the defenses of hyperglycemia-induced neuronal senescence are emerging as promising therapeutic approaches to prevent hyperglycemia-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in animal models, supplementation with polyamines could have a beneficial effect on several age-related disorders including memory decline, neuroinflammation, and cardiovascular disease (107, 180182). Several in vitro studies have shown that the administration of spermidine in cell lines of neuronal origin inhibits the process of cellular senescence (183, 184). It has been proposed that the mechanism by which polyamines produces these beneficial anti-aging effects could be through the activation of autophagy (34, 101), either through the inhibition of the activity of the acetyltransferase EP300, which is involved in the modulation of autophagic flux (185187), or the stabilization of pro-autophagic factors such as MAP1S (179).…”
Section: Dietary Polyamines In Aging and Cancermentioning
confidence: 99%
“… 174 Hyperglycaemia (HG)-induced neurotoxicity leads to the pathogenesis of diabetic encephalopathy and neuronal senescence, while spermidine can prevent HG-induced neurotoxicity and senescence. 81 In a kidney ischemia/reperfusion injury model, spermidine supplementation can markedly attenuate increases in plasma creatinine concentrations and tubular injury, inhibit oxidative stress, and suppress tissue necrosis. 175 The healthy aging effect of spermidine may be related to the enhancement of autophagy.…”
Section: Therapeutic Drugs Targeting Senescencementioning
confidence: 99%